Celastrol inhibits growth and metastasis of human gastric cancer cell MKN45 by down‐regulating microRNA‐21. (16th April 2019) - Yao, Shan‐Shan; Han, Lei; Tian, Zi‐Bin; Yu, Ya‐Nan; Zhang, Qi; Li, Xiao‐Yu; Mao, Tao; Yang, Lin
Abstract : Celastrol could inhibit cancer cell growth in vitro. However, effect(s) of celastrol on gastric cancer is not well studied. Therefore, we investigated the effects of celastrol on human gastric cancer cell line MKN45 and the underlying mechanisms. We found that celastrol inhibited cell proliferation, migration, and invasion and induced cell apoptosis and G2/M cell cycle arrest ( p  < .05, p  < .01, or p  < .001). Under celastrol treatment, overexpression of microRNA‐21 (miR‐21) increased cell viability, migration, and invasion and inhibited cell apoptosis compared with negative control ( p  < .05, p  < .01, or p  < .001). In addition, the phosphorylation of PTEN was significantly up‐regulated, whereas PI3K, AKT, p65, and IκBα phosphorylation was statistically decreased by celastrol ( p  < .05 or p  < .01) and then further reversed by miR‐21 overexpression ( p  < .05 or p  < .01). On the other side, miR‐21 silence showed contrary results ( p  < .05) as relative to miR‐21 overexpression. In conclusion, celastrol inhibits proliferation, migration, and invasion and inactivates PTEN/PI3K/AKT and nuclear factor κB signaling pathways in MKN45 cells by down‐regulating miR‐21.